149 Satisfaction with Food-Related Life Of Irish Adults Older Than 55 Years. (16th September 2019) - Dermiki, Maria; Pope, Jennifer
Abstract: Background: Food is an important part of older people's life contributing to their physiological and mental well-being and to their satisfaction with life. The aim of this study was to investigate the factors that contribute to the satisfaction with food-related life of Irish community-dwelling adults older than 55 years. Methods: A mixed methods approach was employed. Quantitative data were collected through a survey which tested how socio-demographic characteristics, food habits, mood and self-perceived health were correlated (Spearman correlation) with the 5 items from the satisfaction with food-related life (SWFL) questionnaire. Qualitative data were collected through open-ended questions which investigated the factors determining food satisfaction levels of the 81 adults (54 women) older than 55 years who participated in the study. Results: The highest score (4.3/5) was given to the item from the SWFL questionnaire: "F ood and meals are very important elements in my life", and was regardless of gender, age and marital status of the participants. In contrast, the lowest score (3.9/5) was given to the item "M y life in relation to food and meals is ideal ". Spearman's correlation revealed that fruit consumption was positively correlated " With regard to food, the conditions of my life are excellent " (rho=0.29, p<0.05). The open-ended questions showed that sensory appeal was the most popular term related to food satisfaction levels. Conclusion: Meals and food play an important role in older adults' life; however, participants did not consider their life in relation to meals and food as ideal. Therefore, strategies need to be employed to improve food and meal experience for community-dwelling older adults to keep them healthy for longer. Food industry should focus on developing nutritious and sensory-appealing food for the older consumers. Finally, the finding that consumption of fruit leads to satisfaction with food-related life could be used as a health promotion message to change eating behaviour.